Problems and Solution to Diagnose Extrapulmonary Tuberculosis in Central Region of Nepal - Gupta, Ravi Shankar; Khatun, Tarannum; Ansari, Akhtar Alam; Shidiki, Amrullah; Bhargava, Dipak; Gupta, Bidhya; Majumder, Anirban (Med Phoenix, 2017)
Extrapulmonary Tuberculosis is high, challenging the clinicians to make correct diagnosis. Microscopy, culture and fine needle aspiration cytology have their limitations in regard to specificity and sensitivity. In this report, polymerase chain reaction is used for detecting and distinguishing Extrapulmonary Tuberculosis. A case of retropharyngeal abscess was selected from which pus was collected which was negative for microscopy and culture in routine microbiology as well as mycobacteriology. Cytopathological examination was also negative. Polymerase chain reaction was applied to detect Mycobacterium tuberculosis specific IS6110 gene. The patients responded with anti-tuberculosis treatment well. Polymerase chain reaction was introduced for diagnosis of Extrapulmonary Tuberculosis since it can be done within hours, monitor therapy and also differentiate Mycobacterium tuberculosis from other Mycobacterial species. MED Phoenix Volume (1), Issue (1) July 2016, page: 41-43